Las revoluciones de colores - Rodríguez Rodríguez, Angélica (Revista CIDOB d’Afers Internacionals, 2024)
Revista CIDOB d’Afers Internacionals, nº 101 Cuatrimestral (abril 2013) ISSN:1133-6595 | E-ISSN:2013-035X Reseña de libros: Bunce, Valerie J.; Wolchik, Sharon L. Defeating Authoritarian Leaders in Postcommunist Countries. Cambridge University Press, 2011. 396 págs. González Villa, Carlos. Las revoluciones de colores. Eurasian Hub, 2011. 113 págs. Jankovic, Daliborka. After the Color Revolutions. A comparative Analysis of the Democratization. Processes in Georgia, Ukraine, and Kyrgyzstan VDM Verlag Dr. Müller, 2011. 100 págs.